Treatment constraints for single dose external beam preoperative partial breast irradiation in early-stage breast cancer. (October 2017) - Charaghvandi, Ramona K.; Yoo, Sua; van Asselen, Bram; Rodrigues, Anna; van den Bongard, Desirée H.J.G.; Horton, Janet K.
Abstract: Background: Following breast-conserving surgery and post-operative 3D-conformal accelerated partial breast irradiation (APBI), suboptimal cosmetic results have been reported. Preoperative radiation delivery to the intact tumor enables better target visualization and treatment volume reduction. Single dose preoperative APBI has the potential to improve toxicity profiles, reduce treatment burden and enable in vivo exploration of breast cancer radiogenomics. Purpose: Develop practical guidelines for single dose external beam preoperative APBI. Methods: Recommended dose constraints were derived from pooled dosimetry estimates from 2 clinical trials. In an American dose escalation trial, a uniform 15, 18 or 21 Gy dose has previously been evaluated for non-lobular cT1N0 or low/intermediate grade DCIS <2 cm in prone position ( n  = 32). In the Netherlands, the feasibility of ablative APBI (20 Gy to GTV, 15 Gy to CTV) to non-lobular cT1N0 in supine position, is currently being explored ( n  = 15). The dosimetric adherence to the developed constraints was evaluated in new APBI plans with a 21 Gy uniform dose but an extended CTV margin ( n  = 32). Results: Dosimetric data pooling enabled the development of practical guidelines for single dose preoperative APBI. Conclusion: The developed guidelines will allow further explorations in the promising field of single dose preoperative external beam APBI for breast cancer treatment.